2018
DOI: 10.29271/jcpsp.2018.04.279
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas Aeruginosa: Evaluation Of Pathogen Burden And Drug-resistance Trends In A Tertiary Care Hospital

Abstract: Emerging drug-resistant strains of Pseudomonas aeruginosa are probably linked to the injudicious use of antibiotics, leading to ineffective empirical therapy. Therefore, we suggest that culture and antimicrobial susceptibility testing should be done for targeted antimicrobial therapy against Pseudomonas aeruginosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Bessa et al identified PA as one of the main pathogens infecting the respiratory, cutaneous, and urinary tracts [ 32 ]. Saeed et al reported a high frequency of PA in sputum, urine, and wound swab samples [ 33 ]. Similarly, Cabot et al [ 34 ] and Sader et al [ 35 ] found a high prevalence of nosocomial respiratory, urinary, and wound infections due to PA.…”
Section: Discussionmentioning
confidence: 99%
“…Bessa et al identified PA as one of the main pathogens infecting the respiratory, cutaneous, and urinary tracts [ 32 ]. Saeed et al reported a high frequency of PA in sputum, urine, and wound swab samples [ 33 ]. Similarly, Cabot et al [ 34 ] and Sader et al [ 35 ] found a high prevalence of nosocomial respiratory, urinary, and wound infections due to PA.…”
Section: Discussionmentioning
confidence: 99%
“…Although, our results were higher than results obtained by (Sader et al 2017) wherein, the resistance percentage was (84.3%). The sample size, duration, type, and study settings all are possible causes for the variation in the resistance rate (Saeed et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It is found in the recent related literatures that, [1][2][3][4][11][12][13][14][15] the drug resistance of pseudomonas aeruginosa is mostly caused by the gene mutation of its own. In nature, this type of mutation can be manifested as a self-defense mechanism of bacteria, i.e., bacteria can withstand various adverse factors in the environment by encoding the corresponding proteins.…”
Section: Score Of the Regulatory Abilitymentioning
confidence: 99%
“…Pseudomonas aeruginosa is one of the most commonly seen drug-resistance bacteria in the lower respiratory tract infection. It is reported that [1][2][3][4] the drug-resistance genes of pseudomonas aeruginosa mainly consist of some gene families such as mecA/aph/tetM/aac/ermA. In addition, there exist some differences in methylation level, copy number variation, carrying and combination mode as well as transcript of the drug-resistance genes, the high variation of which may be a decisive factor for the drug resistance of pseudomonas aeruginosa.…”
Section: Introductionmentioning
confidence: 99%